2023
DOI: 10.1021/acs.jafc.2c08353
|View full text |Cite
|
Sign up to set email alerts
|

CYP6DW3 Metabolizes Imidacloprid to Imidacloprid-urea in Whitefly (Bemisia tabaci)

Abstract: Bemisia tabaci has developed high resistance to many insecticides and causes substantial agricultural and economic losses annually. The insecticide resistance of whitefly has been widely reported in previous studies; however, the underlying mechanism remains little known. In this study, we cloned two P450 genes: CYP6DW3 and CYP6DW5v1; these genes were markedly overexpressed in imidacloprid-resistant whitefly populations compared with susceptible populations, and knockdown of these genes decreased the imidaclop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…Mobile phases A and B were 80% methanol and 5% ammonium acetate (including 0.1% formic acid). A similar UPLC‐MS/MS condition was adopted with positive ion mode for all analyses as described 34 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile phases A and B were 80% methanol and 5% ammonium acetate (including 0.1% formic acid). A similar UPLC‐MS/MS condition was adopted with positive ion mode for all analyses as described 34 …”
Section: Methodsmentioning
confidence: 99%
“…A similar UPLC-MS/MS condition was adopted with positive ion mode for all analyses as described. 34 2.13 Evaluation of biological fitness associated with the resistance After identification of CYP4CS5 conferring thiamethoxam and clothianidin resistance, we next investigated whether such resistance is accompanied by fitness cost in the whitefly.…”
Section: Metabolism Of Thiamethoxam and Clothianidin In Vitromentioning
confidence: 99%
“…In the past few years, studies into the underlying mechanism of resistance to IMD have made great progress, especially in the adult stages of B. tabaci , in which resistance is caused by the overexpression of P450s. In particular, CYP6CM1 and CYP6DW3 can metabolize IMD both in vitro and in vivo experiments 32–35 . Because of the morphological, behavioral and physiological differences between adult and nymphal whiteflies, little is currently known about the underlying mechanism conferring IMD resistance in these insects.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, CYP6CM1 and CYP6DW3 can metabolize IMD both in vitro and in vivo experiments. [32][33][34][35] Because of the morphological, behavioral and physiological differences between adult and nymphal whiteflies, little is currently known about the underlying mechanism conferring IMD resistance in these insects. 20E, which is an age-specific substance in the immature stage, is particularly important for many biological processes in insects and, as mentioned above, may have a possible role in insecticide resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The key metabolic enzyme cytochrome P450 (P450) plays a crucial role in the detoxification of various xenobiotics, including insecticides . Numerous studies have shown that the induced or constitutive expression of P450 genes in insecticide-resistant insect strains and/or in response to insecticide exposure confers insecticide resistance. , Investigations of the molecular basis of neonicotinoid resistance in whitefly, Bemisia tabaci, revealed that several P450 genes (including CYP6DW3 , CYP6CM1, and CYP4C64 ) are expressed at high levels in resistant strains, and their encoded products play pivotal roles in resistance. Another study identified a cluster of nine CYP6AE subfamily genes encoding products that are capable of detoxifying several xenobiotics (xanthotoxin, 2-tridecanone, and indoxacarb) in vivo . Overexpression of CYP6P9a and CYP6P9b in Anopheles funestus conferred resistance to carbamates, and their encoded products were demonstrated to be able to metabolize carbamates …”
Section: Introductionmentioning
confidence: 99%